The relationship between diversification and manufacturing companies performance in Malaysia / Nur Afizan Abd Latip - Abd Latip, Nur Afizan (2017)
This research paper investigate relationship between diversification and manufacturing companies’ performance in Malaysia. The key performance indicator includes return on asset (ROA), return on equity (ROE) and market return (MR). The diversification measured by Specialization ratio (SR) whereby it classified into three (3) categories: less diversification, moderate diversification and high diversification. The data sample that used in this research are based on panel data approach comprised the data of 120 manufacturing companies listed in Bursa Malaysia within a period of five (5) years from 2012 to 2016. The findings of this study resulted that there is positive relationship between diversification and companies’ performance.